2018
DOI: 10.1186/s40410-018-0079-3
|View full text |Cite
|
Sign up to set email alerts
|

An empirical research study on prospect–refuge theory and the effect of high-rise buildings in a Japanese garden setting

Abstract: This study was carried out to test prospect-refuge theory and the effect of external high-rise buildings on landscape preferences in a traditional Japanese daimyo (feudal lords) garden, namely, the Hama-rikyu Gardens located in Tokyo, Japan. Eight sites in the garden were selected to be tested with respect to their degree of openness, their degree of safety, and the ratio of background buildings present. An in situ survey was conducted with 129 people (15-18 per site) who agreed to take part in the survey. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(56 reference statements)
2
3
0
1
Order By: Relevance
“…In addition, it is found that age and nationality (East Asian or not) had a certain degree of influence on the predictability of SVF, which is consistent with the research results of Senoglu et al [29]. We believe that people of different ages will have different opinions on the renewal and sustainable development of cultural heritage gardens.…”
Section: The Predictability Of View Factor On Preferencessupporting
confidence: 88%
See 3 more Smart Citations
“…In addition, it is found that age and nationality (East Asian or not) had a certain degree of influence on the predictability of SVF, which is consistent with the research results of Senoglu et al [29]. We believe that people of different ages will have different opinions on the renewal and sustainable development of cultural heritage gardens.…”
Section: The Predictability Of View Factor On Preferencessupporting
confidence: 88%
“…Meanwhile, SVF and tourist preferences were positively related; and GVF was negatively correlated. However, BVF did not show any strong correlation, which also validated the research of Senoglu et al, that the visible building index does not explain tourist preferences [29].…”
Section: The Predictability Of View Factor On Preferencessupporting
confidence: 86%
See 2 more Smart Citations
“…Studies dealing with the development of health-promoting green spaces often refer to the qualities that Appleton (1975) emphasizes in his Prospect-Refuge theory (e.g., Senoglu et al, 2018 ). Other authors refer to Orians (1986) and his savannah theory (e.g., Townsend and Barton, 2018 ) or to Wilson (1984) and his biophilia theory (e.g., Browning et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%